Harmful transparency in teams - BAG, Parimal (Institutional Knowledge at Singapore Management University, 2016)
In a two-player team project with efforts over two rounds, we demonstrate that observability of peer efforts can be strictly harmful if preferences are utilitarian. This contrasts with Mohnen et al. (2000) who show in a similar setting that observability of interim efforts induces more efforts, if team members are inequity-averse.